Cycloaddition of N-Sulfonylpyridinium Imides and Isoquinolinium Imides with Acetylenedicarboxylates: A Practical Synthesis of Pyrazolo[1,5-a]pyridine and Pyrazolo[5,1-a]isoquinoline Derivatives - Wu, Chunrui; Wang, Qingbo; Zhao, Jingjing; Li, Pan; Shi, Feng (Synthesis, 2012)
With the introduction of a sulfonyl group on the exocyclic nitrogen, pyridinium imides can undergo smooth [3+2] cycloaddition with electron-deficient alkynes to afford pyrazolo[1,5-a]pyridine derivatives after elimination of the sulfonyl group. The transformation operates with easy-to-handle substrates under mild conditions and brings the yields to a synthetically practical level. In situ generated isoquinolinium imides can also produce pyrazolo[5,1-a]isoquinolines in a similar fashion.
Keywords: dipolar cycloaddition; heterocycles; azomethine imine; pyrazolo[1,5-a]pyridine; tandem reaction